Implementation of Restorative Justice in a Customary Court in Rejang Lebong District, Bengkulu, Indonesia: A Maqāṣid Al-Sharī‘ah Review - Toha Andiko; Zurifah Nurdin; Efrinaldi Efrinaldi (JURIS (Jurnal Ilmiah Syariah), 2024)
This paper aims at analyzing the form of restorative justice implemented in a customary court in Rejang Lebong District, and maqāṣid al-sharī‘ah review of the customary court. This type of research is qualitative with sociological-juridical approach. Data sources were literature, observation, in-depth interviews and documentation. The data analysis technique used qualitative descriptive analysis. This study showed that the form of restorative justice applied in the process customary court in Rejang Lebong prioritizes deliberation and peace between the parties. In terms of sanctions, compensation is based on the request of the victim and the consent of the perpetrator coupled with customary fines. Although there is a provision for customary fines, in practice, the judge determines the amount according to the ability of the perpetrator. In terms of  maqāṣid al-sharī‘ah, the process prioritizing deliberation and peace is relevant to the objective of evading mafsadat, which is to reduce the anger and resentment of the victim or their family. Based on the form of sanctions applied, there is a benefit to maintain the existence of religion, property, soul, offspring, and honor. The sanctions prioritizing restoration, harmonious relations, deterrent effects, and learning for the community, have mutual functions of zawajir and ta'dib. This customary justice model that combines restorative justice and local wisdom can possibly be an alternative dispute resolution to non-litigation case settlement.